Free Will and Retribution Today - De Caro, Mario; Marraffa, Massimo (ETHICS IN PROGRESS, 2014)
The paper addresses two issues that have been recently debated in the literature on free will, moral responsibility, and the theory of punishment. The first issue concerns the descriptive project, the second both the substantive and the prescriptive project. On theoretical, historical and empirical grounds, we claim that there is no rationale for fearing that the spread of neurocognitive findings will undermine the ordinary practice of responsibility attributions. We hypothetically advocate two opposite views: (i) that such findings would cause the collapse of all punitive practices; (ii) that, on the contrary, such findings would open the way to more humane forms of punishment, which would be justified on purely utilitarian grounds. We argue that these views are both wrong, since whereas a sound punitive system can be justified without any reference to moral responsibility, it will certainly not improve the humaneness of punishment.